Investigating the Pedagogical, Technological, and Engagement Constraints of Online Literature Teaching among EFL Learners - Achouak Sellah (My University, 2026)
Abstract This study investigates the pedagogical, technological, and engagement constraints shaping online literature teaching in the EFL context among Master One learners. Despite the growing shift towards virtual instruction in Algerian higher education, online literature teaching has received limited scholarly attention. The study seeks to identify the main challenges students face during online literature lessons, particularly regarding their comprehension of literary texts, participation in discussions, and engagement in virtual learning environments, and to propose practical recommendations to address these constraints. The study is guided by the hypotheses that online literature teaching in the EFL context is shaped by pedagogical, technological, and engagement-related constraints and that students’ pedagogical difficulties during online literature lessons negatively affect their engagement. A mixed-methods approach was adopted, combining a survey, non-participant classroom observation, a focus group discussion with students, and semi-structured interviews with literature teachers at Mohamed Cherif Messaadia University, Souk-Ahras. The findings reveal that limited interaction and low student participation constitute the most pressing concerns, compounded by difficulties in interpreting literary content, poor internet connectivity, and recurring audio disruptions. The study concludes that addressing these issues requires clearer instructional delivery, richer visual and interactive materials, targeted engagement strategies, and stronger institutional technological support. Practical recommendations are proposed to enhance students’ comprehension, interaction, and engagement in online EFL literature classes. ------------------------ الملخص تتناول هذه الدراسة القيود البيداغوجية والتكنولوجية والمتعلقة بالانخراط التي تؤثر في تدريس الأدب عبر الإنترنت في سياق تعلم اللغة الإنجليزية كلغة أجنبية لدى طلبة السنة الأولى ماستر. وعلى الرغم من التوجه المتزايد نحو التعليم الافتراضي في التعليم العالي الجزائري، فإن تدريس الأدب عبر الإنترنت لم يحظ باهتمام علمي كافٍ. تهدف الدراسة إلى تحديد أهم الصعوبات التي يواجهها الطلبة أثناء دروس الأدب عبر الإنترنت، خاصة فيما يتعلق بفهم النصوص الأدبية، والمشاركة في المناقشات، والانخراط في بيئات التعلم الافتراضية، وتقديم توصيات عملية للتعامل مع هذه التحديات. وتستند الدراسة إلى فرضيتين مفادهما أن تدريس الأدب عبر الإنترنت في سياق اللغة الإنجليزية كلغة أجنبية يتأثر بقيود بيداغوجية وتكنولوجية ومتعلقة بالانخراط، وأن الصعوبات البيداغوجية التي يواجهها الطلبة خلال هذه الدروس تؤثر سلباً على مستوى انخراطهم. وقد تم اعتماد منهجية بحث مختلطة تجمع بين الأدوات الكمية والنوعية، من خلال استبيان، وملاحظة صفية غير مشاركة، ومجموعة نقاش مع الطلبة، إضافة إلى مقابلات شبه موجهة مع أساتذة الأدب بجامعة محمد الشريف مساعدية بسوق أهراس. وأظهرت النتائج أن ضعف التفاعل وقلة مشاركة الطلبة يمثلان أبرز المشكلات، إضافة إلى صعوبات في تفسير المحتوى الأدبي، وضعف الاتصال بالإنترنت، وتكرار مشاكل الصوت. وتخلص الدراسة إلى أن تحسين تدريس الأدب عبر الإنترنت يتطلب تقديم شروحات أوضح، واستخدام مواد بصرية وتفاعلية أكثر، واعتماد استراتيجيات فعالة لتعزيز الانخراط، إلى جانب توفير دعم تكنولوجي مؤسساتي أفضل. كما تقدم الدراسة توصيات عملية لتحسين فهم الطلبة وتفاعلهم وانخراطهم في دروس الأدب عبر الإنترنت في سياق اللغة الإنجليزية كلغة أجنبية. -------------------------- Résumé Cette étude examine les contraintes pédagogiques, technologiques et d’engagement qui façonnent l’enseignement de la littérature en ligne auprès des étudiants de Master One dans un contexte EFL. Malgré le recours croissant à l’enseignement virtuel dans l'enseignement supérieur algérien, ce domaine demeure peu exploré. La recherche vise à identifier les défis rencontrés par les étudiants, notamment en matière de compréhension des textes littéraires, de participation aux discussions et d’engagement dans les environnements d’apprentissage virtuels, et à proposer des recommandations pratiques pour y remédier. Elle est guidée par les hypothèses selon lesquelles l'enseignement de la littérature en ligne est influencé par des contraintes pédagogiques, technologiques et d’engagement, et que les difficultés pédagogiques affectent négativement l’engagement des étudiants. Une approche mixte a été adoptée, combinant un questionnaire, une observation non participante, un groupe de discussion et des entretiens semi-directifs avec des enseignants de littérature à l'Université Mohamed Chérif Messaadia de Souk-Ahras. Les résultats révèlent que l'interaction limitée et la faible participation constituent les principales difficultés, aggravées par des problèmes de compréhension du contenu littéraire, de connexion Internet et de qualité audio. L'étude conclut que l'amélioration de cet enseignement nécessite des explications plus claires, des supports visuels et interactifs plus riches, des stratégies d'engagement ciblées et un meilleur soutien technologique institutionnel. Des recommandations pratiques sont proposées pour renforcer la compréhension, l’interaction et l’engagement des étudiants dans les cours de littérature en ligne en contexte EFL.
Keywords: online literature teaching; EFL learners; pedagogical constraints; technological constraints; student engagement; Master One students; تدريس الأدب عبر الإنترنت، متعلمو اللغة الإنجليزية كلغة أجنبية، القيود البيداغوجية، القيود التكنولوجية، انخراط الطلبة، طلبة السنة الأولى ماستر; enseignement de la littérature en ligne; apprenants EFL; contraintes pédagogiques; contraintes technologiques; engagement des étudiants; étudiants de Master One